Reviewing the Pretrial Judge's Decision in Case Number: 04/Pid.Prap/2015/Pn.Jkt.Sel: As a Legal Discovery or Ambivalent Legal Construction - Setyowati, Sulis (UNIVERSITAS PAKUAN, 2023)
The decision of the Pretrial Judge who tried Case Number: 04/Pid.Prap/2015/PN.jkt.Sel became controversial because it included the determination of the suspect in the pretrial object and granted the request of the applicant, Komjen Budi Gunawan, with the main argument of making a legal discovery. The legal problem is whether the legal considerations prepared by the pre-trial judge in examining and deciding the case are correct and whether the pre-trial judge in the a quo case did not exceed the limits of authority in the law. This research is normative legal research with a case approach, statutory approach, conceptual approach and philosophical approach. The research data is in the form of secondary data and processed using qualitative descriptive analysis with deductive thinking logic. The results of the research are 1) in the pretrial lawsuit filed by Budi Gunawan, there is no normative formula that can be used by pretrial judges to assess the validity of the suspect's determination. Considering the formulation of the meaning of Article 1 number 10 jo. Article 77 jo. Article 82 paragraph (1) and paragraph (2) of the Criminal Procedure Code can be seen that whether the suspect's determination is valid or not is not a pretrial object, because it is not regulated. 2) The ambivalence of the pretrial judge's views can be seen in his considerations regarding the meaning of coercive measures as a concept or legal institution.